Nazwy komitetów wyborczych – aspekty strukturalne i aksjologiczne - Naruszewicz-Duchlińska, Alina (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2017)
The subject of this paper will be a semantic and structural analysis of the names of electoral committees, and a reference to the axiological systems that are indirectly reflected by them. The names of electoral committees are obligatory elements of electoral activities, as well as being an interesting element of political marketing.